The Effect of Applying Practical Work Using the Kitchen Preparation Technique to Improve Students' Concept Mastery on the Topic of Hereditary Substances - Ashari, Panji (Universitas Syiah Kuala, 2024)
The purpose of this study is to investigate how students' conceptual comprehension is affected when the